Zum Wechselverhältnis von Orthodoxie und Aufklärung.: G. E. Lessings allegorische Zeitdiagnostik in Herkules und Omphale - Kerber, Hannes (Zeitschrift für neuere Theologiegeschichte, 2018)
Gotthold Ephraim Lessing stands out among the thinkers of the 18th century for his refusal to synthesize theology and philosophy. But due to his notorious ambivalence about religious questions, even Lessing's contemporaries remained uncertain whether he ultimately sided with the former or the latter. The short dialogue Hercules and Omphale is, to the detriment of research on this topic, largely unknown. I show that the dialogue offers in a nutshell Lessing's comprehensive analysis of the intellectual and religious situation of his time. By calling on the mythical travesty of the Asian queen and the Greek hero, Lessing illustrates the mutual attraction that has led astray both Enlightenment philosophy and contemporary Lutheran orthodoxy. Implicitly, his diagnosis of the aberrations of philosophy and theology sheds light on Lessing's own position. The twofold criticism is an attempt to restore theology as well as philosophy in their genuine forms and to reestablish their proper relationship. Through his twofold restitutio in integrum, Lessing is able to reopen the quarrel between orthodoxy and the Enlightenment and, thus, to radically renew the all but forgotten theologico-philosophical antagonism.